Seasonality of first coitus in Northwestern Russia: the importance of location availability - Kozlov MV (Science and Engineering Publishing Company, 2022)
The majority of studies addressing sexual behavior of adolescents were conducted in the USA, which has prevented generalizations to the countries which differ from the USA in social interactions, quality of life and sexual culture. Furthermore, the studies of sexual debut usually explore the role of time availability and supervision, while location availability in some countries may be more important than time availability. The questionnaires filled in by 262 Russian students demonstrated relatively early sexual debut (males: 16.4 years; females: 17.0 years) and strong summer peak of coital activity associated with frequent use of marginally suitable locations. Use of marginally suitable locations was much higher in small villages than in cities, at a younger age, and when sex was by desire rather than by love. These data suggest ‘Location Availability Hypothesis’ partially competing with ‘Summer Vacation Theory’: in summer more sites, including marginally suitable locations, are available for adolescent sexual activity, and the use of these locations contributes to the summer peak in the onset of sexuality.